O programa da compra antecipada da produção em áreas de baixa renda, no estado de Sergipe, 1978: um estudo descritivo - Torres Bandeira, Clódion; G Francis, David; Machado Filho, Francisco; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
The present descriptive study made use of experimental data from a governamental project to increase production of food crops and nutrition of residents in the State of Sergipe. Data were collected in 1978.